HASIL BELAJAR MATEMATIKA DITINJAU DARI BELIEF ABOUT MATHEMATICS SISWA SMP - Reza Rozaqi; Hamdani Hamdani; Rustam Rustam (Universitas Tanjungpura, 2020)
AbstractThe purpose of this study was to determine the results of mathematics learning in terms of beliefs about mathematics of eighth grade students of SMP Negeri 1 Tangaran, Sambas Regency. The form of research used in this study is a survey. The data source used in this study was students of class VIII A of SMP Negeri 1 Tangaran, Sambas Regency, the data obtained in this study were beliefs about mathematics questionnaire, mathematics learning test and interviews from several students. Mathematical learning outcomes in terms of students' beliefs about mathematics show that each student has varying results in learning mathematics. This means that students who have high beliefs about mathematics do not necessarily have high mathematics learning outcomes, students who have moderate beliefs about mathematics do not necessarily have moderate mathematics learning outcomes, and students who have low beliefs about mathematics may not necessarily have low mathematics learning outcomes. Keywords: Belief About Mathematics, Lower Secondary School, Mathematical Learning Outcomes